2020
DOI: 10.1080/13614533.2019.1691026
|View full text |Cite
|
Sign up to set email alerts
|

Librarian, Faculty, and Student Perceptions of Academic Librarians: Study Introduction and Literature Review

Abstract: A survey concerning perceptions of academic librarians was conducted at a large, 4-year university with three populations: librarians, faculty, and undergraduate students. The high response rate and the use of an instrument based on previous studies offers the possibility of longitudinal comparison and the identification of relationships between groups within one environment. Results will be presented in a series of articles, beginning with this paper's study introduction and literature review of librarian, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 82 publications
0
13
0
2
Order By: Relevance
“…(Q4) seemed to align with the services and roles identified in the literature. For example, teaching was rated the most frequently performed duty on this survey, reflecting the strong association with teaching found in the literature (Fagan et al, 2020). JMU organizational priorities also seem to be reflected in the responses.…”
Section: What Librarians Do: Duties and Roles Of Librariansmentioning
confidence: 56%
See 4 more Smart Citations
“…(Q4) seemed to align with the services and roles identified in the literature. For example, teaching was rated the most frequently performed duty on this survey, reflecting the strong association with teaching found in the literature (Fagan et al, 2020). JMU organizational priorities also seem to be reflected in the responses.…”
Section: What Librarians Do: Duties and Roles Of Librariansmentioning
confidence: 56%
“…What librarians know: Librarian expertise and skills/value for librarians' skills Our literature review (Fagan et al, 2020) found copious information about "what librarians know" in research studies of job advertisements. Mentions of technology skills increased over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations